The Legal Triads in Llanstephan MS 116, folios 1–2. (1st December 2019) - Sims-Williams, Patrick
The fragmentary text of the Triads on the first two folios of the fifteenth-century Welsh law manuscript Llanstephan 116 is transcribed and collated with similar legal texts.